Textures, fabrics and meltlayer stratigraphy in the Hans Tausen ice core, North Greenland - indications of late Holocene ice cap generation? - Nørgaard Madsen, Karen; Thorsteinsson, Thorsteinn (Meddelelser om Grønland. Geoscience, 2001)
A thin section study of crystal structure has been carried out on a 345 m long ice core drilled to bedrock on Hans Tausen Iskappe, 1995. In addition a meltlayer stratigraphy was set up, showing how the fraction of meltlayer-ice in the core increases with depth. Main characteristics of crystal structure are increasing mean crystal size from top to bottom in the core and development of a weak single maximum c-axis fabric. The rate of ice crystal growth in the well dated upper half of the core is much lower than expected from studies of the normal grain growth regime in other polar ice cores. Probably the grain boundary movements are impeded by impurities, which are present in relatively high concentrations in the Hans Tausen ice. Asuming the applicability of the calculated growth rate throughout the core, a late Holocene origin of the oldest ice is suggested by the size of the crystals close to bedrock. Presented data furthermore implies that bottom ice temperatures were never near the melting point and it is concluded that there was no ice cap on the Hans Tausen plateau earlier in Holocene.